2018
DOI: 10.1590/s0100-204x2018000200012
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with glutamine or glutamic acid for weanling piglets

Abstract: The objective of this work was to evaluate the effects of dietary glutamine and glutamic acid supplementation on carbon turnover (δ13C) in the muscles of piglets, on animal performance, and on feed economic feasibility. The diets consisted of: control (C), 1% glutamine (G), and 1% glutamic acid (GA). In experiment I, 111 piglets were used to assess carbon turnover in the Masseter, Psoas major, and Abdominal internal oblique muscles in terms of their isotopic composition and 13C substitution over time. In exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…In spite of the positive effects of glutamine on small intestinal villus morphology and plasma net xylose absorptive concentration in 28-day-old weaning pigs, 1% or 2% glutamine supplementation in a corn-soybean meal diet did not significantly affect growth performance during the 21-day treatment period (Hsu et al, 2010). Similar results were obtained by (Amorim et al, 2018) who also did not observe any significant effects of 1% glutamine or 1% glutamate on growth performance variables in pigs fed a rice grit and…”
Section: Glutamine Regulates Intestinal Function Of Weaning Pigssupporting
confidence: 88%
See 1 more Smart Citation
“…In spite of the positive effects of glutamine on small intestinal villus morphology and plasma net xylose absorptive concentration in 28-day-old weaning pigs, 1% or 2% glutamine supplementation in a corn-soybean meal diet did not significantly affect growth performance during the 21-day treatment period (Hsu et al, 2010). Similar results were obtained by (Amorim et al, 2018) who also did not observe any significant effects of 1% glutamine or 1% glutamate on growth performance variables in pigs fed a rice grit and…”
Section: Glutamine Regulates Intestinal Function Of Weaning Pigssupporting
confidence: 88%
“…Glutamine had the adverse effect of weaning on growth, villus height but not totally overcoming the stress of weaning on intestinal structure and function Wang et al (2014) 21 days old Mixtures of glutamine and glutamate (the ratio between glutamine and glutamate was unknown); five treatments: basal diet supplementation with 0, 0.5%, 1.0%, 1.5% mixtures and positive control (basal diet þ4% porcine plasma) for 21 days in corn and soybean meal-based diet soybean-based diet. Different diets, weaning age, experimental duration or dosage of glutamine may contribute to differing growth performance responses to glutamine or glutamate supplementation (Kitt et al, 2002;Di et al, 2003;Amorim et al, 2018).…”
Section: Glutamine Regulates Intestinal Function Of Weaning Pigsmentioning
confidence: 99%
“…Several studies reported that some feed additives, such as plant extracts, exogenous enzymes, and GLU, had beneficial effects on growth performance and gut barrier functions of pigs [ 8 , 14 , 15 , 28 ]. In particular, GLU is regarded as one of the most promising performance-enhancing additives with amino acid synthesis properties [ 8 ]. However, the correlations of dietary GLU on growth performance and intestinal barrier and immune functions of pigs are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in agreement with previous studies, suggesting that dietary GLU may give more beneficial effects on growth performance of weaned pigs around the first 10 to 21 days after weaning [ 9 , 29 , 30 ]. These results indicate that dietary GLU promotes the growth performance of pigs by increasing feed intake and performing as a metabolic fuel that more effectively increases cell turnover rate during intestinal development [ 8 , 9 ]. Moreover, it is well known that GLU has umami properties that may have an important role in the taste, palatability, and acceptability of the feeds [ 6 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation